Drone-based photogrammetry reveals differences in humpback whale body condition and mass across North Atlantic foraging grounds - Chelsi Napoli; Nathan Hirtle; Julia Stepanuk; Fredrik Christiansen; Eleanor I. Heywood; Thomas J. Grove; Alyssa Stoller; Flordespina Dodds; Maria Glarou; Marianne H. Rasmussen; Gina L. Lonati; Kimberley T.A. Davies; et al. (Frontiers in Marine Science, 2024)
Baleen whales are key consumers in marine ecosystems and can serve as ecosystem sentinels. Body condition, defined as an individual’s energy stores relative to its structural size, can provide a useful proxy for health in baleen whales. As capital breeders, important life history events in baleen whales such as seasonal migrations and reproduction depend on having sufficient energy stores. Spatiotemporal variability of body condition of baleen whales can reflect differences in energy accumulated during the foraging season. Here we assess and compare the body condition and mass of humpback whales ( Megaptera novaeangliae) across four different foraging areas from the West Indies distinct population segment in the Northwest Atlantic. Morphometric measurements of humpback whales were obtained using unoccupied aerial systems (UAS, or drones) from the New York Bight, the Gulf of Maine, Iceland, and Greenland. Uncertainty in morphometric estimates was incorporated and propagated using a bootstrapping approach. Measurements were used to estimate body volume and calculate a body condition index (BCI) for each individual whale. Since body mass is a key parameter for understanding animal physiology and bioenergetics, we further compared whale body mass to body size between foraging areas by converting body volume to body mass using estimates of tissue density from tagging studies. BCI showed significant differences between foraging areas with a large effect size (ANCOVA: mean η 2 = 0.168; all p< 0.001) when incorporating day of year and year as covariates. Humpback whales in the Gulf of Maine showed significantly higher BCI than those in the New York Bight, Iceland, and Greenland. Standardized Major Axis (SMA) regressions comparing log-log relationships of both body volume and body mass, respectively, to total length reinforced these results. Humpback whales in the Gulf of Maine showed significantly higher elevation in the SMAs than those in the other study regions (p<0.001), implying that humpback whales foraging in the Gulf of Maine accumulated greater energy reserves for a given body size. Estimates of body mass indicate that for a given body length, humpback whales in the Gulf of Maine have an 18% greater body mass than those in the New York Bight, Iceland, or Greenland. Regional differences in prey availability or anthropogenic threats could contribute to the observed patterns in body condition. Our findings highlight the importance of regional environmental factors to the nutritional health of baleen whales.